Flexible ureteroscopy: Technological advancements, current indications and outcomes in the treatment of urolithiasis - Husain Alenezi; John D. Denstedt (Asian Journal of Urology)
The last 3 decades have witnessed great improvements in the technology and clinical applications of many minimally invasive procedures in the urological field. Flexible ureteroscopy (fURS) has advanced considerably to become a widely utilized diagnostic and therapeutic tool for multiple upper urinary tract pathologies. The most common indication for fURS is the treatment of upper urinary tract stones with the aid of Holmium:Yttrium Aluminium Garnet (YAG) laser lithotripsy. Advancements in endoscope technologies and operative techniques have lead to a broader application of fURS in the management of urolithiasis to include larger and more complex stones. fURS has proved to be an effective and safe procedure with few contraindications. Continued progression in fURS may increase its clinical applicability and supplant other procedures as the first line treatment option for urolithiasis.